Pengembangan Modul Biologi Berbasis Praktikum Pada Materi Keanekaragaman Hayati Kelas X Di SMA Tahfiz Al Batthawi Kerongkong: Development of Biology Modules Based on Practical Work on Biodiversity Material for Grade X at SMA Tahfiz Al-Batthawi Kerongkong, Suralaga District, East Lombok Regency - Ahmad Fadli; Siti Wardatul Jannah; Nening Listari (Otus Education: Jurnal Biologi dan Pendidikan Biologi, 2024)
This study aims to develop a practicum based biology module  for class X SMA Tahfiz Al-Batthawi NWDI Kerongkong. In this development research refers to the ADDIE development model which is carried out through five stages, namely analysis, design, development, implementation, and evaluation. The product developed was validated and assessed by 1 material expert and 1 media expert. The limited trial in this study was given to 15 students of class X. The instruments in this study were a check list questionnaire and evaluation questions. Data analysis was carried out by scoring using a Likert scale, then calculating the average of each aspect. The results of the assessment of material experts are 85% and the results of the assessment of media experts are 93%. While the results of the student response questionnaire in the very feasible category, namely 85%. Thus, this module is suitable to be used as a teaching material in the biology learning process.